An energetics–performance framework for wild fishes. Issue 1 (16th May 2022) - Brownscombe, Jacob W.; Raby, Graham D.; Murchie, Karen J.; Danylchuk, Andy J.; Cooke, Steven J.
Abstract: There is growing evidence that bioenergetics can explain relationships between environmental conditions and fish behaviour, distribution and fitness. Fish energetic needs increase predictably with water temperature, but metabolic performance ( i.e ., aerobic scope) exhibits varied relationships, and there is debate about its role in shaping fish ecology. Here we present an energetics–performance framework, which posits that ecological context determines whether energy expenditure or metabolic performance influence fish behaviour and fitness. From this framework, we present testable predictions about how temperature‐driven variability in energetic demands and metabolic performance interact with ecological conditions to influence fish behaviour, distribution and fitness. Specifically, factors such as prey availability and the spatial distributions of prey and predators may alter fish temperature selection relative to metabolic and energetic optima. Furthermore, metabolic flexibility is a key determinant of how fish will respond to changing conditions, such as those predicted with climate change. With few exceptions, these predictions have rarely been tested in the wild due partly to difficulties in remotely measuring aspects of fish energetics. However, with recent advances in technology and measurement techniques, we now have a better capacity to measure bioenergetics parameters in the wild. Testing these predictions will provide a more mechanistic understanding of how ecological factors affect fish fitness and population dynamics, advancing our knowledge of how species and ecosystems will respond to rapidly changing environments.